Performance optimization of wireless sensor network for multimedia services - Karamat Khan, Tehmina; Shah, Asadullah; Muhammed Yusof, Zulkefli (Science Publishing Corporation, 2018)
WSN multimedia services are currently being used by several types of applications. These services experiences performance related issues in the form of slow data rates, packet loss etc. due to stringent resources. Lots of solutions are contributed to develop a system that optimizes the resources utilization, performance and packet loss. Performance evaluation for enhancing QoS of WSN is also required where packets arrive and depart the service facility (sink) in burst. In this paper, novel analytical approach is developed for packets arri-val from sensor node in burst and departure of services after getting the facility, in burst. The evaluation has been performed by shifting coefficient of variance for the time when services are provided in burst and when services are arrived on different scales of utilization of the sink node. At the end of this paper quantitative results are compared after applying priority to data packets to check credibility of proposed solution.